Knowledge, attitudes, and practices of nurses caring for surgical cerebral aneurysm patients in a Thai Tertiary Hospital - Sobut, Palama; Wongpimoln, Boonyada; Pleaynongkhae, Supattra; Hanlue, Kitiyarat; Udonsat, Sattawas (Intelektual Pustaka Media Utama, 2025)
Ruptured cerebral aneurysm after surgery is a critical condition that necessitates vigilant monitoring and early detection of complications by staff nurses. Therefore, an appropriate level of skill and knowledge related to the management of patients undergoing surgery is crucial for nurses to support these patients. The current research aimed to examine KAP indicators (knowledge, attitude, and practice) among nurses in this context, making use of a cross-sectional study design involving the participation of 111 staff nurses selected randomly from one tertiary hospital located in the northeast of Thailand. The study was carried out during February – June 2024, making use of a survey to acquire demographic data along with a questionnaire to measure the KAP indicators. Data were analyzed using the Spearman correlation coefficient and Pearson correlation coefficient. The finding revealed that the overall KAP score on caring patients with ruptured cerebral aneurysm undergoing surgery was high. However, the correlation observed between knowledge/attitude/age/duration of experience for caring patients with ruptured cerebral aneurysm undergoing surgery and practice was shown to be both positive and significant (p<0.05). Therefore, nurse administrators should implement a comprehensive knowledge training system, enhance specialized training, and improve nursing practices for these patients. This will help to ensure that staff nurses achieve a high level of KAP in providing optimal care for these patients.